Testing, modelling and design of concentrically-loaded concrete-encased concrete-filled steel tube slender column - Wu, Nuoxin (2023)
Concrete-encased concrete-filled steel tube (CECFST), an innovative type of concrete-steel composite structure, has been increasingly employed in mega construction projects due to its outstanding structural performance. However, although intermediate and sometimes slender columns have become commonplace in high-rise buildings and large-scale bridges, the research on member behaviour of CECFST slender columns barely exists in the current literature. In this paper, a comprehensive experimental and numerical modelling programme was conducted to study buckling resistance and structural behaviour of CECFST slender columns. Pin-ended concentric load column tests were carried out on four slender columns, together with a fixed-ended stub column as a reference specimen. Key test results of all specimens, such as failure modes and effects of slenderness on strength, ductility and stiffness, showed that buckling failure and P-δ effect degraded the performance indices of CECFST slender columns. Afterwards, a finite element (FE) modelling programme was performed, where a range of member imperfections was incorporated and validated against test results. Parametric studies were then conducted to supplement the test data bank, from which over sixty FE results were generated. The test and FE failure loads obtained were utilised to examine the applicability of current design methods in the European code, American specification and Australian standard. The buckling curve 'b' set out in the European code was found to result in the most accurate and consistent buckling resistance predictions, while the American specification and Australian standard generally yielded over-conservative and unsafe results, respectively.